ANALISIS TINGKAT KESELAMATAN LALU LINTAS PADA PERSIMPANGAN DENGAN METODE TRAFFIC CONFLICT TECHNIQUE - Muslimin, Eviliona; Rudi, Rudi; Ranuang, Trianto (Universitas Bina Taruna Gorontalo, 2024)
Abstract: Analysis of Traffic Safety Levels at Intersections Using the Traffic Conflict Technique Method. In this research, to determine the characteristics of traffic accidents which are influenced by human factors as road users at intersections using the Traffic Conflict Technique method with field surveys to obtain information to support data analysis to get an overview of the types of conflicts that have the greatest potential to cause accidents. From the results of the serious conflict research, the shortest time was 0.27 Time To Accident and the longest time was 0.63 Time To Accident, with driver speeds of 20km/hour, 25km/hour, 30 km/hour and 35km/hour. Motorbikes have the greatest conflict with the nature of the driver who does not pay attention to the safe distance between vehicles so that the rider cannot take evasive action long before reaching the point of conflict.